Software development to anonymize patient information from clinical computed tomography images - Anam, Choirul; Naufal, Ariij; Saragih, Jhon Hadearon; Ali, Mohd Hanafi (International Journal of Public Health Science (IJPHS), 2024)
A free software for digital imaging and communications in medicine (DICOM) image anonymization is needed to protect patient information from third parties. This study aimed to develop a software for the anonymization of patient information in computed tomography (CT) image. There was a total of 17 informations to be anonymized, such as Patient’s Name, Other Patient Names, Patient’s ID, Patient’s Birth Date, Patient’s Sex, Patient’s Age, Study ID, Study Description, Series Description, Institution Name, Institution Adress, Referring Phisician’s Name, Consulting Physician’s Name, Performing Physician’s Name, Name of Physician(s) Reading Study, Operator’s Name, and Protocol Name. In every information, its initial value was replaced with a dummy value with the string value of "N/A". For testing, patient CT images from four different hospitals with different scanners were collected. It is found that each scanner had different information stored in DICOM information. However, the anonymization process in the four hospitals works well with accuracy of 100%. The developed software can anonymize DICOM images flexibly and successfully. This software can be used for anonymization of patient information in order to protect patient information.